Correlation between History of Fall and Timed Up and Go Test in Geriatric - Nurmalasari, Mifta; Widajanti, Novira; Dharmanta, Rwahita Satyawati (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. Fall is the global major problem in geriatrics as it causes physical and physicological impairment, even leads to mortality. Timed up and go test (TUG) is the screening method which commonly used in medical practice as standard examination to assess mobility, balance, and fall risk.This study aimed to determine the correlation between TUG and history of falls in geriatric patients at General Hospital Dr. Soetomo Surabaya, Indonesia. Methods. A cross-sectional study was conducted among geriatric patients in Dr. Soetomo hospital with criteria ≥ 60 years old, mini mental state examination (MMSE) score ≥ 17, did not suffer from hemiplegic stroke, and did not use walking aids. Subjects with these criteria were interviewed to know the fall history from the past 12 months, level of education, and comorbidity. Then the subjects carried out MMSE assessment, BMI (body mass index) measurement, and TUG assessment. Statistical analysis was done with Fisher exact test.. Results. A total of 73 subjects participated in this study of which 56.16% were women. Among 73 subjects, 18 subjects had a history of falls and 72.22% of them were women. The Fisher test results showed a significant relationship between history of falls and TUG with p value= 0.048 and a contingency coefficient= 0.305. Conclusion. There was weak correlation between history of falls and TUG. Subsequent studies need to add and select samples with uniform distribution of characteristics, so that the results could represent the entire elderly population at General Hospital Dr. Soetomo Surabaya, Indonesia.